Tissue Microstructure Is Linked to MRI Parameters and Metabolite Levels in Prostate Cancer - Selnæs, Kirsten Margrete; Vettukattil, Riyas; Bertilsson, Helena; Wright, Alan J.; Heerschap, Arend; Angelsen, Anders; Tessem, May-Britt; Bathen, Tone Frost (Frontiers in Oncology, 2016)
Introduction: Magnetic resonance imaging (MRI) can portray spatial variations in tumor heterogeneity, architecture and its micro environment in a non-destructive way. The objective of this study was to assess the relationship between MRI parameters measured on patients in vivo, individual metabolites measured in prostatectomy tissue ex vivo and quantitative histopathology. Materials and methods: Fresh frozen tissue samples (n=53 from 15 patients) were extracted from transversal prostate slices and linked to in vivo MR images, allowing spatially matching of ex vivo measured metabolites with in vivo MR parameters. Color-based segmentation of cryosections of each tissue sample was used to identify luminal space, stroma and nuclei. Results: Cancer samples have significantly lower area percentage of lumen and higher area percentage of nuclei than non-cancer samples (p≤0.001). Apparent diffusion coefficient is significantly correlated to percentage area of lumen (ρ=0.6, p<0.001) and percentage area of nuclei (ρ=-0.35, p=0.01). There is a positive correlation (ρ=0.31, p=0.053) between Citrate and percentage area of lumen. Choline is negatively correlated to lumen (ρ =-0.38, p=0.02) and positively correlated to percentage area of nuclei (ρ =0.38, p=0.02). Conclusion: Microstructures that are observed by histopathology are linked to MR characteristics and metabolite levels observed in prostate cancer.